2013
DOI: 10.9755/ejfa.v25i6.15514
|View full text |Cite
|
Sign up to set email alerts
|

Performance and hematological parameters of broilers fed neem, turmeric,<br>vitamin e and their combinations

Abstract: An experiment was conducted to study the efficiency of inclusion of neem, turmeric, vitamin E and its combinations on performance and hematological parameters for a period of six weeks with 288 day old Raja II broiler chicks. Basal diet was supplemented with Azadirachta indica (Neem 8g/kg feed), Curcuma longa (Turmeric 2g/kg feed) and Vitamin E 0.2g/kg feed) individually and in combination to form eight test diets. Each test diet was fed ad libitum for 42 days. The result of the present stumdy identified no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 11 publications
0
13
2
Order By: Relevance
“…The significant biological properties of curcumin render it a potential substitute for antibiotics in livestock feed. A number of studies have been conducted to evaluate the effects of curcumin on the performance of broiler chickens (Suriya et al, 2012;Nayaka et al, 2013;Abou-Elkhair et al, 2014;Olukosi and Dono, 2014); however, the results of these studies have been inconsistent. Keeping in view of the medicinal attributes of C. longa, the purpose of the present study was to evaluate the effects of increasing levels of turmeric rhizome extract (TRE) on performance, carcass characteristics, antioxidant capability, and meat quality of Wenchang broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…The significant biological properties of curcumin render it a potential substitute for antibiotics in livestock feed. A number of studies have been conducted to evaluate the effects of curcumin on the performance of broiler chickens (Suriya et al, 2012;Nayaka et al, 2013;Abou-Elkhair et al, 2014;Olukosi and Dono, 2014); however, the results of these studies have been inconsistent. Keeping in view of the medicinal attributes of C. longa, the purpose of the present study was to evaluate the effects of increasing levels of turmeric rhizome extract (TRE) on performance, carcass characteristics, antioxidant capability, and meat quality of Wenchang broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Neem is the most useful traditional medicine as a source of many therapeutic agents in the Indian culture and grows well in the tropical and semi-tropical countries. It has been shown that neem leaves extract acts as a growth promoter [ 7 ], improve performance and hematological parameters [ 8 ] and immune response [ 9 , 10 ] in broilers. In indigenous system of medicine, every part of the neem tree, viz .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing heterophils count after administration of birds neem meal recorded previously by (Esonu et al, 2006;Nayaka et al, 2013). Administration of neem aqueous extract combining with vaccination and/or infection induced insignificant increase in heterophils count in compare with groups vaccinated or infected only may be resulted from the possible protection action of neem against heterophils apoptosis as NDV exhibit high-level of apoptosis (Ravindraa et al, 2009).The result of this study agrees with (Obianuju et al, 2015).…”
Section: Discussionmentioning
confidence: 55%